Engagement with life among the oldest-old in assisted living facilities: enriching activities and developmental adaptation to physical loss. Issue 5 (26th May 2022) - Boeder, Jordan; Hwang, Sarah; Chan, Thomas
Abstract: The objective of this study was to examine the activities, motivations, and barriers of activity engagement in the oldest-old residing in assisted living facilities (ALFs). Semi-structured interviews were conducted with 20 participants, aged 80–94 (standard deviation = 4.38), from two ALFs. Thematic analyses were used to identify and corroborate clusters of experiences. All residents stated that they desired enriching activities, most often in the form of productive work or community events. Although engaging in enriching activities was a universal desire, residents who experienced more functional limitations had an increased difficulty satisfying this need. Participants believed that activities offered by the ALF primarily served those who are cognitively impaired. ALF residents with severe mobility issues were not able to access more enriching activities outside the ALF compared to those with fewer physical limitations. However, the more physically impaired residents used a range of adaption methods that fit into the selection, optimisation, and compensation framework to overcome barriers to participate in meaningful activities. ALF residents who are cognitively fit but experience severe mobility limitations may be the most in need of enriching activities. To help these residents maintain a high quality of life, ALFs need to provide activities that appeal to residents of varying cognitive abilities and provide interventions to help aid their adaption to physical loss.